The temporal evolution of the ratio HNO3/NOy in the arctic lower stratosphere from January to March 1997 - Schneider, J.; Arnold, F.; Ziereis, H.; Feigl, C.; Lelieveld, J.; Scheeren, H. A.; Bujok, A. A.; Curtius, J.; Sierau, B.; Fischer, H.; Hoor, P.; Wienhold, F. G.; et al. (Geophysical Research Letters, 1999)
Aircraft-based measurements of HNO3, NOy, N2O, and O-3 have been performed in the Arctic lower stratosphere in January (POLSTAR I) and March (STREAM III) of 1997. The two projects employed different aircraft platforms. In addition, NOy and O-3 were measured using different instruments in the two campaigns. HNO3 and NOy were found strongly correlated with correlation coefficients of 0.84 (POLSTAR I) and 0.69 (STREAM III), respectively. The fraction of HNO3 within NOy decreased from 96% in January to 59% in March. The decrease is consistent with the lifetime of HNO3 due to photolysis after polar sunrise. The relationship of NOy and HNO3 with N2O shows that in January NOy and HNO3 values were markedly higher than expected, which may indicate nitrification by PSC-II particle sedimentation and evaporation. Contradictory, the ratios NOy/O-3 observed in January are only slightly elevated. In March, NOy-N2O and NOy-O-3 relations agree well with others reported in the literature. The difference between the NOy-O-3 and NOy-N2O relationships is partly explained by an observed O-3 decrease of about 30% between January and March.